Biosynthesis, characterization, and antibacterial activity of ZnO nanoaggregates using aqueous extract from Anacardium occidentale leaf: comparative study of different precursors - Droepenu, Eric Kwabena; Asare, Ebenezer Aquisman; Wee, Boon Siong; Rafeah, Wahi; Ayertey, Frederick; Kyene, Odoi Michael (Springer, 2021)
Background Various parts of Anacardium occidentale plant possess curative qualities like antidiabetic, anti-inflammatory, antibacterial, antifungal, and antioxidant. Aqueous extract of this plant leaf was used in biosynthesizing zinc oxide (ZnO) nanoaggregates using two precursors of zinc salt (zinc acetate dihydrate [Zn(CH3COO)2∙2H2O] and zinc chloride [ZnCl2]). The synthesized ZnO samples were used in a comparative study to investigate the antibacterial activity against selected Gram-positive and Gram-negative microbes [Staphylococcus aureus, Exiguobacterium aquaticum (Gram +ve) and Escherichia coli, Klebsiella pneumoniae, Acinetobacter baumannii (Gram −ve)]. The synthesized ZnO nanoaggregates from the two precursors were characterized using Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy-dispersive x-ray spectroscopy (EDX) techniques.